A Microplate Format for Characterizing the Growth of Molybdenum-reducing Bacteria (Journal of Environmental Microbiology and Toxicology, 2014)
Molybdenum is toxic to ruminants and the process of spermatogenesis in catfish and mice. The bioremediation of heavy metals including molybdenum is being intensely studied. More efficient reducers are being isolated. An advantage of microbial molybdate reduction to molybdenum blue is the intense blue product absorbs wavelength strongly in the far red region whilst cells without the addition of molybdenum showed little absorption in this region. This means that no sample treatments such as centrifugation are needed and the readings can be taken straight away. In this work we developed a microplate or a microtiter plate assay for monitoring molybdenum blue production from a bacterium. The molybdenum blue produced when measured from a microplate gave about 2 times less absorbance intensity compared to measurement using a normal cuvette, but is adequate for characterization works as the absorbance obtained was 0.886 compared to 1.709 for measurement using cuvette. The development of microplate format for monitoring microbial reduction to molybdenum blue is simple to perform and would ensure works on the characterizations of novel molybdenum reducers can potentially be carried out in a few days instead of a few weeks.
Keywords: toxicity; charaterization